A qualitative study on sexual and reproductive health needs and risks of adolescents in Bidibidi refugee settlement, Uganda - George Palattiyil; Hadijah Mwenyango; Dina Sidhva; Peter Kisaakye; Harish Nair; Paul Bukuluki (Global Social Challenges Journal, 2025)
Introduction: Sexual and reproductive health (SRH) is an important global health issue linked to the United Nations Sustainable Development Goals. Adolescents in refugee settings face specific SRH needs and risks, and limited access to needed services. This research, therefore, aimed to develop an understanding of SRH needs of, and risks to, adolescent refugees, to inform adolescent sexual and reproductive health policies and programmes. Methodology: The study employed qualitative approaches. Seventeen in-depth interviews were conducted with adolescent refugees and nine key informant interviews with stakeholders, including representatives from NGOs, health facility workers and refugee leaders. We performed content and thematic analysis drawing on the ecological systems theory framework. Findings: Reproductive health issues presented by adolescent refugees included menstruation supplies, reproductive health education and contraception. Participants reported several reproductive health risk factors that include risky sexual relationships, child abuse in homes, early marriage, teenage pregnancies and forced marriage, and sexual and gender-based violence. Conclusion: The findings highlight significant gaps in adolescent refugees’ knowledge and access to SRH services. These gaps are shaped by cultural norms, limited service availability, and lack of targeted SRH education for young people in refugee settings. Recommendation: Targeted training is vital to guaranteeing efficient delivery of SRH services; with humanitarian organisations ensuring their personnel is appropriately trained to support adolescent refugees and their SRH needs. Culturally appropriate services are required to ensure greater buy-in and build trusting relationships with the population.